APLIKASI MARKA MOLEKULER PADA BUAH DAN BIJI KOPI ASAL KALIMANTAN TIMUR [Molecular marker application of cherry and green bean of East Kalimantan coffee] - Fatimah, Fatimah; Urnemi, Urnemi; Mustopa, Apon Zaenal; Syahrumsyah, Hudaida (BERITA BIOLOGI, 2014)
Two quantitative traits, cherry and green bean characters are the important phenotypic selection in coffee breeding practice. The important well-known character from coffee markets is cherry and bean size. In this study, 43 genotypes of coffee were collected from four districts in East Kalimantan i.e. Kutai Kertanegara, Kutai Timur, Berau dan Paser Utara. The objective of this study was to identify cherry and green bean character using quantitative trait locus (QTL) molecular marker, genetic variation from developed alleles, cluster analysis and association analysis of molecular marker, and phenotype observation. Based on polymorphic information content (PIC) of primers used in this study, the genetic variation was low. Based on cluster analysis, two major groups were identified. The first group corresponds to Arabika that consisted of 3 districts, Kutai Timur, Berau and Paser Utara. The second group correspond to Robusta mostly from Kutai Kertanegara.Significant association of primer markers M480 and M312 with QTL has suggested that they can be used as specific primers linked to size of cherry and green bean.Furthermore,they were potential marker assisted breeding in coffee breeding program.